Taxonomia e biologia populacional de duas espécies simpátricas de Hyalella (Crustacea, Amphipoda, Hyalellidae) - Limberger, Marcio (2020)
Freshwater amphipods of the genus Hyalella are typical in American continental waters and have high levels of endemicity. In Brazil, the state of Rio Grande do Sul has the greatest diversity of species for the genus known so far. This work describes a new species, Hyalella n. sp., which occurs in sympathy with H. gauchensis in a spring in the municipality of Palmeira das Missões, southern Brazil. In Hyalella n. sp. the following characters were observed: antenna 2 with a length that covers more than half of the total body size, gnathopod 2 has an irregular palm with a elongated propodus, inner ramus of the male uropod 1 with absence of the apical curve setae, uropod 3 peduncle with seven strong distal spattered setae with accessory setae and ramus with ten cuspidate setae and with accessory setae. Hyalella n. sp. occurs in sympathy with H. gauchensis, but these differ especially in shape and size from gnathopod 2, presence of curved setae in the uropod 1 of males in H. gauchensis and absence in Hyalella n. sp., antenna length (largest in Hyalella n. sp.) and number of cuspidated setae in the uropods 1, 2 and 3. According to this work, the number of Hyalella species found in Brazil is 29 and 13 for the state of Rio Grande do Sul. Since these amphipods are important indicators of environmental quality in the ecosystems where they inhabit, it is of great importance to have knowledge about the biology and population dynamics of these organisms for conservation measures. However, so far there have been few ecological studies about Hyalella species from Brazil. These studies could help to assess the impacts of various human activities on freshwater environments. Besides the taxonomic description, this work analyzed the population dynamics and reproductive aspects of two Hyalella morphotypes (Hyalella gauchensis and Hyalella n. sp.) that live in sympathy in a spring found in the northwestern region of the state of Rio Grande do Sul, Brazil. The collections were carried out during a period of 12 months (April 2018 to March 2019) lasting 10 minutes per collection with hand net by one person and transported to the laboratory. All individuals sampled were sexed, measured and separated by cephalothorax (CC) length size classes during all months, and both morphotypes showed bimodal distribution in most seasons, except the females of H. gauchensis that showed polimodal distribution. H. gauchensis had a higher abundance and higher average cephalothorax length when compared with Hyalella n. sp.. In both species, males body size (CC) was greater than that of females, although they occur in smaller numbers. Both H. gauchensis and Hyalella n. sp. had their peak breeding and recruitment during the colder seasons of the year (winter and autumn, respectively), indicating that the temporal separation these behaviors between the two populations may highlight different strategies and/or evolutionary adaptations for them to coexist.